Smart Grid Data Security Aggregation Method Based on Fog Computing Architecture for Integrated Energy Services. Issue 1 (June 2020) - Chang, Su; Ge, Song; Yining, Gang; Zhenxian, Yao
Abstract: Integrated energy systems incorporate new types of clean and distributed energy into the power grid. In the future, smart grid will emerge in the form of integrated energy services. However, the application of new technology inevitably brings the threat of privacy disclosure. To deal with this kind of information security, a smart grid data security aggregation technology based on fog computing architecture for integrated energy services is proposed in this paper. Real-time data is encrypted in the energy acquisition equipment to obtain the first layer of privacy protection, and fine-grained aggregation at the fog end to obtain the second layer of privacy protection, so as to achieve the confidentiality and privacy of the entire network data transmission and processing. Finally, the safety and performance evaluation shows that this technology has a great advantage over other schemes in terms of safety, practicability and efficiency.